Guide to Assessing Health Care Organizations : Quality, Safety, Ethics - International Finance Corporation (Washington, DC, 2015)
In recent years, International Finance Corporation (IFC) has become increasingly active in the private health sector in developing countries. We are now the largest multi-lateral investor in the private health sector, worldwide. Since 2000 the author have provided over US$1.5 billion of financial support (mainly through debt and equity financing) to over 80 projects in more than 30 countries. This support has enabled some $4 billion of investment in the private health sector. Health care organizations supported by IFC provide employment for around 35,000 people and treat 5.5 million patients annually. About one third of our clients are based in IDA countries (mainly poorer developing countries). And about one fifth of our clients have achieved some form of internationally recognized accreditation. This guide is intended to assist IFC staff to undertake an on-site assessment of the quality of care and safety of the hospital environment. The guide complements the commercial due diligence (which covers, for example, business, financial, legal and insurance issues). Some essential aspects of Facility Safety (e.g. fire precautions etc.) are covered; however, the guide does not replace IFC’s separate environmental, life and fire safety assessment.